2007
DOI: 10.1021/la701007j
|View full text |Cite
|
Sign up to set email alerts
|

Primary versus Ternary Adsorption of Proteins onto PEG Brushes

Abstract: Polyethylene glycol (PEG) brushes are used to reduce protein adsorption at surfaces. Their design needs to allow for two leading adsorption modes at the brush-coated surface. One is primary adsorption at the surface itself. The second is ternary adsorption within the brush as a result of weak PEG-protein attraction. We present a scaling theory of the equilibrium adsorption isotherms allowing for concurrent primary and ternary adsorption. The analysis concerns the weak adsorption limit when individual PEG chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
151
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(162 citation statements)
references
References 62 publications
11
151
0
Order By: Relevance
“…Some studies have pointed out that most of the known surfaces resistant to single-protein solutions were decorated with kosmotrope moieties [172,204], which could prevent the approach of a protein by a long-range interaction with the protein water shell [205]. Other studies have reported on the effect of architecture, configurational entropy, and elasticity of polymer chains in a brush [6,[36][37][38][206][207][208]. The search for the interfacial water structures associated with some structural motifs and gradients in density and mobility of polymer chains throughout the polymer brush in relation to the fouling resistance continues to be a challenge for current research on antifouling surfaces.…”
Section: Discussion Of Approaches To Design Novel Low-fouling Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have pointed out that most of the known surfaces resistant to single-protein solutions were decorated with kosmotrope moieties [172,204], which could prevent the approach of a protein by a long-range interaction with the protein water shell [205]. Other studies have reported on the effect of architecture, configurational entropy, and elasticity of polymer chains in a brush [6,[36][37][38][206][207][208]. The search for the interfacial water structures associated with some structural motifs and gradients in density and mobility of polymer chains throughout the polymer brush in relation to the fouling resistance continues to be a challenge for current research on antifouling surfaces.…”
Section: Discussion Of Approaches To Design Novel Low-fouling Coatingsmentioning
confidence: 99%
“…Protein adsorption on a substrate with a low-fouling coating results from a competition between repulsive forces produced by the coating and adhesion forces induced both by interactions between proteins and the substrate surface and by weak attractive interactions between proteins and the coating [36][37][38][39][40]. There are several characteristics related to the physical structure and properties of the coating (thickness, density, elasticity, etc.)…”
Section: Concept Of Antifouling Coatings For Biosensorsmentioning
confidence: 99%
“…Neutron reflectometry in combination with isotopic substitution of hydrogen for deuterium ("contrast variation") may be used to distinguish the nature of adsorption of proteins in polymer brush layers, by building profiles of the polymer and protein in the direction normal to the grafting surface [37]. However, there are many difficulties in trying to understand the complexities and mechanisms that underlie protein resistance due to the lack of contrast between PEO and a hydrogenous protein.…”
Section: Poly(ethylene Oxide) Brushesmentioning
confidence: 99%
“…Molecular simulations have also shown that PEO will hydrogen bind with lysine peptides a common constituent of many proteins [31]. Therefore, the possibility of a tertiary or secondary adsorption of protein at PEO brushes has also been proposed to explain these results, in particular theory work by Halperin et al where an n-cluster type model is demonstrated [32,33]. It has also been found experimentally that methyl-PEG brushes become protein binding at high grafting density, whereas hydroxyl-PEG brushes do not, causing some to speculate a secondary adsorption at the edge of the polymer brush in the secondary position is possible, either promoted by the methyl end groups or conversely deterred by the hydroxyl groups [18,34], see fig.…”
Section: Introductionmentioning
confidence: 99%